Analisis Strategi Integrated Marketing Communication dan Marketing Mix pada Pemasaran PT. Bank Riau Kepri Capem Tangkerang - M Ariq Zafri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research was conducted in the form of an internship process to observe how the use of integrated communication strategies (IMC) and marketing mix carried out by PT Bank Riau Kepri. The data collection method is carried out through a process in the form of an interview process used to analyze the data needed through the results of the interview. Then the observation process is carried out by directly observing the author accompanied by reference sources in the form of journals, books and articles as supporting media in the success of the observation process. The results that have been shown in this study are how the application of advertising and promotion, public relations, direct and digital marketing in PT Bank Riau Kepri for observation of IMC. As well as how the application of the 4P strategy namely product, price, place and promotion (Marketing Mix) implemented by PT. Bank Riau Kepri.